Expression of the apelin receptor, a novel potential therapeutic target, and its endogenous ligands in diverse stem cell populations in human glioblastoma - Williams, Thomas L.; Nwokoye, Peter; Kuc, Rhoda E.; Smith, Kieran; Paterson, Anna L.; Allinson, Kieren; Maguire, Janet J.; Davenport, Anthony P. (Frontiers in Neuroscience, 2024)
Glioblastoma multiforme (GBM) is one of the most common and lethal forms of brain cancer, carrying a very poor prognosis (median survival of ~15 months post-diagnosis). Treatment typically involves invasive surgical resection of the tumour mass, followed by radiotherapy and adjuvant chemotherapy using the alkylating agent temozolomide, but over half of patients do not respond to this drug and considerable resistance is observed. Tumour heterogeneity is the main cause of therapeutic failure, where diverse progenitor glioblastoma stem cell (GSC) lineages in the microenvironment drive tumour recurrence and therapeutic resistance. The apelin receptor is a class A GPCR that binds two endogenous peptide ligands, apelin and ELA, and plays a role in the proliferation and survival of cancer cells. Here, we used quantitative whole slide immunofluorescent imaging of human GBM samples to characterise expression of the apelin receptor and both its ligands in the distinct GSC lineages, namely neural-progenitor-like cells (NPCs), oligodendrocyte-progenitor-like cells (OPCs), and mesenchymal-like cells (MES), as well as reactive astrocytic cells. The data confirm the presence of the apelin receptor as a tractable drug target that is common across the key cell populations driving tumour growth and maintenance, offering a potential novel therapeutic approach for patients with GBM.We have added 'potential' here in accordance with the request from Reviewer 1.We have also added 'potential' here to reflect the change to the title suggested by Reviewer 1.